2020
DOI: 10.3389/fcell.2020.566617
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Promotes Hair Growth by Augmenting TERT Expression

Abstract: Although thinning hair and alopecia are not recognized as severe diseases, hair loss has implications for mental health and quality of life; therefore, a large number of studies have been carried out to develop novel hair growth agents. In the present study, we aimed to examine the potential of telomerase reverse transcriptase (TERT), because TERT overexpression in skin activates resting hair follicle bulge stem cells, which triggers initiation of a new hair follicle growth phase and promotes hair synthesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…RNA was extracted from cells and skin samples using the High Pure RNA Isolation Kit (Roche Diagnostics GmbH, Mannheim, Germany) and RNeasy Fibrous Tissue Mini Kit (Qiagen, Hilden, Germany), respectively, according to the manufacturers’ instructions. cDNA synthesis and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) were performed, as described previously [ 3 , 10 ]. Samples were analyzed in triplicate, and gene expression levels were normalized to the corresponding β-actin gene level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA was extracted from cells and skin samples using the High Pure RNA Isolation Kit (Roche Diagnostics GmbH, Mannheim, Germany) and RNeasy Fibrous Tissue Mini Kit (Qiagen, Hilden, Germany), respectively, according to the manufacturers’ instructions. cDNA synthesis and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) were performed, as described previously [ 3 , 10 ]. Samples were analyzed in triplicate, and gene expression levels were normalized to the corresponding β-actin gene level.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed in triplicate, and gene expression levels were normalized to the corresponding β-actin gene level. The PCR primer sequences were described previously [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that fisetin stimulates hair growth. When applied topically in C57BL/6 mice, fisetin acts on hair growth by stimulating the transition from telogen to anagen phase, effect related to its activity on TERT (telomerase reverse transcriptase) expression in the dorsal skin cells of treated mice (Kubo et al, 2020).…”
Section: Sulfuretinmentioning
confidence: 99%
“…Unsaturated omega-3 fatty acids, present in fish oil, and omega-6, which are found in vegetable oils, play a significant role in maintaining the proper redox balance in cells. Fermented fish oil (FFO) has been shown to reduce ROS production and inhibit MMPs [158]. Vegetable fats also have a beneficial effect on skin conditions.…”
Section: Fatty Acidsmentioning
confidence: 99%